2008
DOI: 10.1350/ijps.2008.10.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention to Reduce Complaints: An Australian Victoria Police Initiative

Abstract: ’Complaints profiling’, ‘early warning’ or ‘early intervention’ systems are currently seen as vital mechanisms for reducing police misconduct and improving police–community relations. This paper reports on the introduction of an early intervention system for police in the State of Victoria, Australia. The findings support the contention that such systems have a demonstrable utility in reducing complaints. A sample of 44 individuals profiled showed that interventions resulted in a 71.07 per cent reduction in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Public opinion survey results, percent with ‘full/quite a lot of trust & confidence in police’, 2008/09 to 2017/18. Source: New Zealand Police (2019b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Public opinion survey results, percent with ‘full/quite a lot of trust & confidence in police’, 2008/09 to 2017/18. Source: New Zealand Police (2019b).…”
Section: Resultsmentioning
confidence: 99%
“…In a second with-in group study, in the state of Victoria Australia, the introduction of an EI system was associated with a reduction in complaints (internal and external) of 71% over two years, involving 44 officers flagged with multiple complaints (Macintyre et al, 2008). The Victorian study included financial cost-benefit data, with an estimated saving of AU$3.2 million in reduced complaint processing costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper drew on multiple sources to attempt to explain, and draw lessons from, the very large and sustained reductions in complaints against AFP ACT officers over the last 15 years. Previous research of this type, including in the Australian state of Tasmania, has shown strong associations between reduced complaints and point-in-time innovations in behavioural management techniques (Charette, 1993;Davis, et al, 2005;Macintyre, et al, 2008;Porter, et al, 2012;Prenzler, et al, 2016;Walker, et al, 2001). In the case of the present study, these correlations were not as clear.…”
Section: Discussionmentioning
confidence: 99%
“…In Victoria, Australia, the deployment of an EIS in 1997 led to a 71% reduction in complaints over a two-year period against 44 officers with multiple complaint histories (Macintyre, Prenzler & Chapman, 2008). The main area of improvement was in allegations of duty failure and minor assault.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this strategy might lead to the establishment of supervision programs for police offi cials. Th is can be seen in the case of Australia where the Victoria Police used reports recorded by citizens to create an early warning scheme of police offi cials (Macintyre, Prenzler & Chapman, 2008). By doing this, complaints fi led by citizens about a particular police offi cial accumulate to warn of potential and severe misconduct committed by that police offi cer.…”
Section: Police Institutional Reformmentioning
confidence: 99%